Effect of Ni addition on corrosion resistance of FePC bulk glassy alloy. (September 2015) - Ma, X. H.; Zhang, L.; Yang, X. H.; Li, Q.; Huang, Y. D.
Abstract : Bulk glassy alloys (BGAs) of Fe80−x Nix P13 C7 ( x = 0, 5, 15 and 25 at.-%) with the diameters up to 2·5 mm were prepared by the combination method of fluxing treatment and J-quenching technique. The effect of replacing Fe by Ni on corrosion resistance of the present Fe based BGAs was systematically investigated by immersion test and potentiodynamic polarisation in 1M HCl and 0·6M NaCl solutions. The results show that, except for Fe80 P13 C7, the corrosion rate of almost the present Fe based BGAs in both 1M HCl and 0·6M NaCl solutions are on the order of 10 −1 mm/year and the corrosion current density in these two solutions decreased from 10 −3 to 10 −6 A cm −2 and 10 −5 to 10 −6 A cm −2, respectively, with increasing Ni content from x = 0 to 25. The corrosion resistances for all the present Fe based BGAs are as good as or superior to that of N80 stainless steel. It is indicated that the corrosion resistance of the present Fe based BGAs increased with the amount of Ni in both solutions. The SEM/EDS analysis shows that the enrichment of Ni oxide in the passive surface layer is responsible for the increased corrosion resistance with the Ni content in the present Fe based BGAs.